2014
DOI: 10.14737/journal.aavs/2014/2.9.508.515
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Previously used CIDR Stored for a Prolonged Period

Abstract: | This study investigated the efficiency of the previously used controlled internal drug release (CIDR) stored for 30 days before reusing. In the first experiment, twenty seven Holstein cows at the day of estrus (day 0) received either no treatment (control), new or reused CIDR and blood samples were collected at day 0, 1, 3 and 7. At day 1 and 3, serum progesterone concentration in cows received new CIDR (1.417 and 1.616 ng/ml) was significantly higher than in cows received a reused one (0.545 and 0.954 ng/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…The standard approach to evaluate blood P 4 concentration is to include ovariectomized cows and/or intact cows in estrus as the basis (18). As the number of usages of the CIDR devices increased, delivered blood P4 concentrations linearly decreased, especially after the 2nd use ( Table 2).…”
Section: Blood Progesterone Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard approach to evaluate blood P 4 concentration is to include ovariectomized cows and/or intact cows in estrus as the basis (18). As the number of usages of the CIDR devices increased, delivered blood P4 concentrations linearly decreased, especially after the 2nd use ( Table 2).…”
Section: Blood Progesterone Concentrationmentioning
confidence: 99%
“…P 4 concentrations. More specifically, the absorbability of P 4 may also vary by the estrus cycle stage due to alterations in the vaginal membrane (18). Interrelationships among body weight, feed intake, and milk yield, leading to alterations in hepatic blood flow and steroidal hormone metabolism, are well established (3,18).…”
Section: Blood Progesterone Concentrationmentioning
confidence: 99%
“…The current trial estimated no significant difference in embryonic loss rate between the Ovsynch and both CIDR‐based protocols. Others recorded a similar embryonic loss rate between the CIDRsynch and Ovsynch protocols in cyclic or anovulatory cows (Abdallah & Abd El Rahim, ). On the contrary, previous trials indicated that embryonic loss rates using the CIDRsynch were significantly lower than those reported with the Ovsynch protocol in anovular cows (Chebel et al, ).…”
Section: Discussionmentioning
confidence: 72%
“…In anestrus cattle, the cost of this estrus synchronization protocol can be further reduced to US $14.57, as PGF2α is not necessary in the absence of CL. Additionally, the prospect of reusing a used CIDR device [60] makes the protocol worthwhile.…”
Section: Discussionmentioning
confidence: 99%